MECHANISM FOR ORGANIZING THE GRANT FINANCING PROCESS OF BUSINESS ENTITIES - Кобеля-Звір, Мар’яна; Вовчак, Ольга (SWorldJournal, 2023)
The article discloses the grant mechanism for targeted financing of business entities in war and wartime conditions. It has been demonstrated that the basis of the mechanism of grant provision of business entities is the systematic unification of certain